A directed genome evolution method to enhance hydrogen production in Rhodobacter capsulatus - Barahona, Emma; Isidro, Elisa San; Sierra-Heras, Laura; Álvarez-Melcón, Inés; Jiménez-Vicente, Emilio; Buesa, José María; Imperial, Juan; Rubio, Luis M. (Frontiers in Microbiology, 2022)
Nitrogenase-dependent H2 production by photosynthetic bacteria, such as Rhodobacter capsulatus, has been extensively investigated. An important limitation to increase H2 production using genetic manipulation is the scarcity of high-throughput screening methods to detect possible overproducing mutants. Previously, we engineered R. capsulatus strains that emitted fluorescence in response to H2 and used them to identify mutations in the nitrogenase Fe protein leading to H2 overproduction. Here, we used ultraviolet light to induce random mutations in the genome of the engineered H2-sensing strain, and fluorescent activated cell sorting to detect and isolate the H2-overproducing cells from libraries containing 500,000 mutants. Three rounds of mutagenesis and strain selection gradually increased H2 production up to 3-fold. The whole genomes of four H2 overproducing strains were sequenced and compared to that of the parental sensor strain to determine the basis for H2 overproduction. No mutations were present in well-characterized functions related to nitrogen fixation, except for the transcriptional activator nifA2. However, several mutations mapped to energy-generating systems and to carbon metabolism related functions, which could feed reducing power or ATP to nitrogenase. Time-course experiments of nitrogenase derepression in batch cultures exposed mismatches between nitrogenase protein levels and their H2 and ethylene production activities that suggested energy limitation. Consistently, cultivating in a chemostat produced up to 19-fold more H2 than the corresponding batch cultures, revealing the full potential of the selected H2 overproducing strains.